The Role of Customer Satisfaction and Brand Image on Customer Loyalty of Cellular Telecommunication Operator Company - Sherry Adelia; Miranti Pradipta Utami; Sarwo Eddy Wibowo; Ratnawita; Sudianto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study intends to examine the impact of brand image and customer satisfaction variables on Telkomsel Sim Card customers' customer loyalty (Y). Analysis is conducted using multiple linear regression. 60 participants made up the sample for this study, who were chosen from Telkomsel SIM Card users using a purposive sampling technique. The findings of this study suggest that brand image and customer satisfaction variables have an impact on customer loyalty at the same time. The findings of this study also demonstrate that customer happiness and brand image have a limited impact on customer loyalty. According to the adjusted R square analysis, brand image and customer happiness account for 60.1% of the relationship between customer loyalty and explanations, with other factors not included in the research model accounting for the remaining 39.9%.